Efektivitas perilaku organisasi dan manajemen strategik terhadap tingkat produktivitas organisasi - Asaari, Masagus; Sandhi, Agung Fitra; Anggiani, Sarfilianty (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Achievement of organizational goals is evidence of the productivity of an organization, which is expected to be able to provide benefits to society both in terms of quality and quantity. The achievement of efficient and effective organizational productivity is, of course, initiated by the performance of various organizational components. The character of organizational members will shape organizational behavior, and organizational leadership styles are also possible to influence the performance of its members, which then has an impact on organizational productivity. The purpose of this research is to obtain information about the effectiveness or not of organizational behavior and strategic management in influencing organizational productivity. The method used is descriptive-quantitative, with data collection techniques such as observation, interviews, documentation, and the distribution of questionnaires to 100 respondents. Based on the results of the study, which stated that organizational behavior has a positive and significant influence so that it is effective in increasing the productivity of organizations in Jakarta with an influence value of 49.2%, strategic management is known to be able to provide a significant and positive influence so that it is effective in increasing organizational productivity in Jakarta by 57.2%.